2013
DOI: 10.1080/19440049.2013.829246
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of brominated flame retardants in black thermo cups and selected kitchen utensils purchased on the European market

Abstract: In order to screen for the presence of a recycled polymer waste stream from waste electric and electronic equipment (WEEE), a market survey was conducted on black plastic food-contact articles (FCA). An analytical method was applied combining X-ray fluorescence spectrometry (XRF) with thermal desorption gas chromatography coupled with mass spectrometry (thermal desorption GC-MS). Firstly, XRF spectrometry was applied to distinguish bromine-positive samples. Secondly, bromine-positive samples were submitted for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(48 citation statements)
references
References 27 publications
2
46
0
Order By: Relevance
“…The annual production of brominated flame retardants is around 200,000 tons [3]. Moreover, investigations have shown that these flame retardants find their way back into our lives as contaminants in material recycled plastics [4,5]. Chemical recycling of such plastics is frequently used for the recovery of monomers and fuel and it is likely that extremely toxic brominated dibenzodioxins and dibenzofurans are produced under pyrolytic conditions [6e8].…”
Section: Introductionmentioning
confidence: 99%
“…The annual production of brominated flame retardants is around 200,000 tons [3]. Moreover, investigations have shown that these flame retardants find their way back into our lives as contaminants in material recycled plastics [4,5]. Chemical recycling of such plastics is frequently used for the recovery of monomers and fuel and it is likely that extremely toxic brominated dibenzodioxins and dibenzofurans are produced under pyrolytic conditions [6e8].…”
Section: Introductionmentioning
confidence: 99%
“…Especially in recycled plastics, the ingoing hazardous substances are often unknown. There is evidence that WEEE has been used for production of polymeric food-contact articles sold on the European market and that these articles contained BFRs (Puype et al, 2015;Samsonek and Puype, 2013). Since most recycling of plastics takes place outside of the Nordic countries and largely also outside of the EU, the plastics that we export for recycling could potentially come back as parts of imported products .…”
Section: Hazardous Impurities and Contaminants In Plasticsmentioning
confidence: 99%
“…Such equipment will continue to reach end-of-life and enter the waste value chain for years to come. The recycling of WEEE plastics containing these chemicals, as is currently reported as widespread for PBDEs under the EU POPs regulation (UNEP, 2010), will contribute to further spread of the chemicals, and may be a source also to human exposure if waste streams are not kept under tight control (Samsonek and Puype, 2013). Moreover, novel chemicals with potential hazardous properties are continuously placed on the market and are gradually replacing known hazardous substances (see EPA, 2014).…”
Section: Rohs and Hazardous Substancesmentioning
confidence: 99%